If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 2y + 24 = 14 + -3y Reorder the terms: 3 + 24 + 2y = 14 + -3y Combine like terms: 3 + 24 = 27 27 + 2y = 14 + -3y Solving 27 + 2y = 14 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 27 + 2y + 3y = 14 + -3y + 3y Combine like terms: 2y + 3y = 5y 27 + 5y = 14 + -3y + 3y Combine like terms: -3y + 3y = 0 27 + 5y = 14 + 0 27 + 5y = 14 Add '-27' to each side of the equation. 27 + -27 + 5y = 14 + -27 Combine like terms: 27 + -27 = 0 0 + 5y = 14 + -27 5y = 14 + -27 Combine like terms: 14 + -27 = -13 5y = -13 Divide each side by '5'. y = -2.6 Simplifying y = -2.6
| (g-4.1)(5.7)= | | 18/-13=n/31 | | x^3+5x^2+ax+2=0 | | 64x-8y=20 | | 280=ab^10 | | 21-2x/5=4-x | | 3(8-5y)+2y=11 | | -18=x^2-11x | | 10x-5(3x+12)=-125 | | 5x+4-x=32 | | 5/9(47)= | | 10x+90=50 | | 10z+90=70 | | 4+4b-4a+4b= | | 3a^2-26a=16 | | 3a^2-26a-16=0 | | (2x+5)(x-3)=8 | | (14-11)+(6+5)= | | 3x^2-6x-2=11 | | t/3-5=13 | | 2(2x+5)-3(x-5)=12 | | (2x+5)(x-3)=9 | | 5-25/17 | | 3x/x-2 | | 12x+36=6x*8 | | 4-20/17 | | 12x+36=6x*.8 | | 6x-2y=-34 | | 21X-21/8/7x-7/72 | | .4(15x-20)=3(3x-4) | | f(x)=-0.02x^2+1.4x+5.3 | | 12/5x=4-x |